2023
DOI: 10.1111/hiv.13533
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical activity on endothelial function in people living with HIV

Andrej Preveden,
Petar Čolović,
Enis Garipi
et al.

Abstract: IntroductionDecreased physical activity is a major cardiovascular risk factor that is particularly pronounced in people living with HIV (PLHIV), who are more susceptible to endothelial dysfunction and accelerated atherosclerosis than the general population due to multiple mechanisms. The aim of the present study was to analyse whether regular physical activity is capable of improving endothelial function measured by flow‐mediated dilatation (FMD) in PLHIV.MethodsWe performed FMD measurement in 38 PLHIV, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…401 A recent study investigating the impact of physical activity (self-reported) on endothelial function in PLWH demonstrated that physical activity was a positive, independent predictor of FMD. 402 Limitations of the study included a cross-sectional design, self-report of physical activity as opposed to objective assessment, and a modest sample size (n=38). Nonetheless, the conclusion drawn from this study is that physical activity is an accessible and cost-effective method to potentially enhance endothelial function and overall cardiovascular health in PLWH.…”
Section: Effects Of Exercise On Vascular Function In Plwhmentioning
confidence: 99%
“…401 A recent study investigating the impact of physical activity (self-reported) on endothelial function in PLWH demonstrated that physical activity was a positive, independent predictor of FMD. 402 Limitations of the study included a cross-sectional design, self-report of physical activity as opposed to objective assessment, and a modest sample size (n=38). Nonetheless, the conclusion drawn from this study is that physical activity is an accessible and cost-effective method to potentially enhance endothelial function and overall cardiovascular health in PLWH.…”
Section: Effects Of Exercise On Vascular Function In Plwhmentioning
confidence: 99%